Mathematics achievement: the relationship between student engagement, parental involvement, and peer influence - Abu Bakar, Nora’asikin; Mohd Ayub, Ahmad Fauzi; Ahmad, Nor Aniza; Syed Abdullah, Sharifah Intan Sharina (Human Resource Management Academic Research Society, 2021)
Mathematics is an important subject as a skill and foundation to further learning at the university level. In this regard, the engagement of students in the learning of mathematics is required so that mathematical knowledge and skills can be learned and mastered as much as possible. Previous study showed that student engagement, parental involvement, and peer influence affect mathematics achievement at a university. The purpose of this is to examine the relationship between mathematics achievement, the three aspect of student engagement, parental involvement, and peer influence. Data were collected from a total sample of 284 undergraduate students at a private university in Malaysia. Descriptive statistics and multiple regression analyses were used to analyse the data. Mathematics achievement was positively related to cognitive engagement and affective engagement, while behavioural engagement did not affect their achievement. Parental involvement and peer influence, on the other hand, are negatively related with mathematics achievement. More studies that concentrated on the relationship between parental involvement, peer influence, and student engagement in the future are encouraged to establish students' engagement in mathematics learning that vital to increase their mathematics achievement. A qualitative study should be considered in order to obtain more information from respondents.